Benchmarking Organic Thin Film Transistors and the Selective Wavelength Exposure of Carbon Nanotube Transistors - Dallaire, Nicholas (Université d'Ottawa / University of Ottawa, 2023)
Carbon based semiconductors such as conjugated polymer or single walled carbon nanotubes (SWNT) are promising materials for use next generation printable and wearable electronics. Thin film transistors (TFTs) are often viewed as a building block for more complex electronic device, however, lack of proper characterization of these devices using these novel carbon-based materials is preventing their large-scale adoption. This thesis has two sections; in the first section I explored and improved a novel electrical model originally developed for organic or polymer-based TFTs called the organic virtual source emission diffusion model (OVSED). I improved this model by adding a variable contact resistance parameter and effective gate voltages. I then found better agreement between model and experimental data using this improved OVSED model against the conventional MOSFET based models: the SH and Y-function models, for poly{[N,N'-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5'-(2,2'-bithiophene)} (P(NDI2OD-T2)) based OTFTs. The new model proved to be an efficient tool for benchmarking polymer based TFTs and provided an efficient way to characterize and reduce contact resistance in the devices. In the second section, I explore the effect of light on a series of conjugated polymer wrapped SWNT TFTs. A structure property relationship was established between the wrapping polymer structure and the exposure wavelength intensity. We demonstrated that SWNT TFTs can act as photodetectors after an initial light soak. Finally, we further characterized the SWNT TFTs using our OVSED model validating the observed structure property relationship. Overall this thesis demonstrates steps towards proper characterization of emerging carbon based semiconductors used in TFTs. -- Les semi-conducteurs à base de carbone, tels que les polymères conjugués ou les nanotubes de carbone à paroi simple (SWNT), sont des matériaux prometteurs pour la prochaine génération d'appareils électroniques imprimables et portables. Les transistors à couche mince (TFT) sont souvent considérés comme un élément de base pour des dispositifs électroniques plus complexes, mais la caractérisation incorrecte de ces dispositifs utilisant ces nouveaux matériaux à base de carbone empêche leur adoption à grande échelle. Cette thèse comporte deux sections ; dans la première, j'ai exploré et amélioré un nouveau modèle électrique développé à l'origine pour les TFT organiques ou à base de polymères, appelé le modèle de diffusion d'émission de source virtuelle organique (OVSED). J'ai amélioré ce modèle en ajoutant un paramètre de résistance de contact variable et des tensions de grille effectives. J'ai ensuite constaté une meilleure concordance entre le modèle et les données expérimentales en utilisant ce modèle OVSED amélioré par rapport aux modèles conventionnels basés sur les MOSFET : les modèles à fonction SH et Y, pour les OTFT à base de poly{[N,N'-bis(2-octyldodecyl)-naphtalène-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5'-(2,2'-bithiophène)} (P(NDI2OD-T2)). Le nouveau modèle s'est avéré être un outil efficace pour comparer les TFT à base de polymères et a fourni un moyen efficace de caractériser et de réduire la résistance de contact dans les dispositifs. Dans la deuxième partie, j'explore l'effet de la lumière sur une série de TFT à base de SWNT enveloppés de polymères conjugués. Une relation structure-propriété a été établie entre la structure du polymère enveloppant et l'intensité de la longueur d'onde d'exposition. Nous avons démontré que les SWNT TFT peuvent agir comme des photodétecteurs après une imprégnation initiale de lumière. Enfin, nous avons caractérisé les SWNT TFT à l'aide de notre modèle OVSED en validant la relation structure-propriété observée. Dans l'ensemble, cette thèse démontre les étapes vers une caractérisation appropriée des semi-conducteurs émergents à base de carbone utilisés dans les TFT.
Keywords: semiconductor; carbon nanotubes; thin film transistors; modelling; laser; photosensor